Steroid hormone levels in postmenopausal hysterectomised women with and without ovarian conservation: the continuous endocrine function of the ovaries - Elsa Nunes; Eugenia Gallardo; Sara Morgado-Nunes; José Fonseca-Moutinho (Journal of Obstetrics and Gynaecology, 2023)
This study aims to clarify the effect of postmenopausal bilateral oophorectomy on plasma steroid hormone levels. Women who were submitted in the postmenopausal period to hysterectomy for uterine benign conditions were divided into two groups: 18 women had isolated hysterectomy and 11 had hysterectomy with bilateral salpingo-oophorectomy. In both groups serum hormone levels were quantified by solid phase extraction and gas chromatography and tandem mass spectrometry. Differences in dehydroepiandrosterone (DHEA), testosterone, androstenedione and oestradiol were determined in both groups. The analysis revealed lower steroid levels in the bilateral salpingo-oophorectomy group when compared to the isolated hysterectomy group with statistically significant differences found for DHEA (5.8 ± 3.2 vs. 9.4 ± 4.4 ng/mL; p = 0.019) and oestradiol (0.69 ± 0.4 vs. 1.48 ± 4.3 ng/mL; p = 0.007). The results are consistent with a significant endocrine activity of the postmenopausal ovary. The clinical consequences of these findings need to be clarified and postmenopausal prophylactic bilateral salpingo-oophorectomy re-evaluated.IMPACT STATEMENT What is already known on this subject? Although it is consensual that premenopausal prophylactic bilateral oophorectomy should not be performed because it has harmful effects on women's health, the evidence regarding the effects of postmenopausal prophylactic bilateral oophorectomy is scarce and this procedure continues to be a regular practice. Few studies have demonstrated that postmenopausal ovaries still have endocrine activity that may impact older women's health. What do the results of this study add? This is the first study to compare hormone levels of postmenopausal women based on their hysterectomy and oophorectomy status using GC-MS/MS, a highly sensitive bioanalytical assay for the measurement of steroid hormones. Previous studies relied on immunoassays and did not compare DHEA levels, which according to the intracrinology theory is a precursor for androgens and oestrogens. In this study, statistically significant lower levels of DHEA and oestradiol were found after postmenopausal bilateral salpingo-oophorectomy. What are the implications of these findings for clinical practice and/or further research? This is a pilot study that may lead to further investigation in this area to clarify the impact of the prophylactic removal of postmenopausal ovaries on older women′s health and lead to changes in surgical procedures.